Rainwater harvesting: types, components and background in arid zones of Mexico as a strategy of sustainable use of water - Jalife Acosta, Sandra (Centro Universitario de Arte, Arquitectura y Diseño, 2018)
A descriptive investigation is developed on the subject of recruitment, types and components of rainwater. A history of work done at national and regional level is presented. The focus is given to arid and semi-arid zones of Mexico, specifically to  the  so-called  “Chihuahuan  desert”,  once  the  water resource in these becomes invaluable due to the little or no disposition of it, for which to identify  and  develop  strategies  for  the  recruitment and the use of this resource becomes fundamental  for  the  development  of  the  different  activities and also impacts on the quality of life of  the  inhabitants.  It  is  concluded  that  there  is  still work to develop on the subject of rainwater collection  and  use  in  arid  and  semi-arid  zones  and that this is presented as a viable strategy for  its implementation and use of the efficient use of this resource. This is the first of three articles; the following are the experimental results of the capture and quality of the water captured by means of these systems. A descriptive investigation is developed on the subject of recruitment, types and components of rainwater.